Effect and Determination of Oxide Trapped Charge and Interface Trapped Charge Density of Threshold Voltage Shift in Irradiated MOSFET by Subthreshold Methodology - Ruangphanit, Anucha; Muanghlua, Rangson; Wongprasert, Yothin (My University, 2023)
This paper presents the effects and determination of oxide and interface trapped charge density of threshold voltage shift in irradiated MOSFET by subthreshold methodology. The designed dimension, channel width per channel length (W/L) is 20 µm/20 µm. The threshold voltage is extracted by a linear extrapolation methodology. The over all threshold voltage shifts are caused by oxide trapped charge and interface trapped charge. The subthreshold methodology determines the interface trapped charge. The60Co gamma-ray source was used for irradiation to a total dose of 10 kGy. The results showed that the threshold voltage shift is approximately-24 mV/kGy for NMOS and-27 mV/kGy for PMOS. The subthreshold swing shift is approximately 1.2 mV/dec.kGy for NMOS and 0.9 mV/dec.kGy for PMOS. The oxide trapped charge density NOT and interface trapped charge density NIT are found to be increased in NMOS and PMOS respectively. The ratio of ΔNOT/ΔNIT was approximately 2.2 times for NMOS and 2.8 times. Due to the structure, the channel of NMOS is a surface channel whereas the channel of PMOS is a buried channel. Finally, the effect of gamma irradiation on the PMOS was greater than the effect on NMOS observed from the change in threshold voltage and the ratio of ΔNOT/ΔNIT..
Keywords: NMOS; PMOS; Subthreshold; Threshold voltage